Evaluation of Concordance Between Deficient Mismatch Repair and Microsatellite Instability Testing and Their Association with Clinicopathological Features in Colorectal Cancer - Bai, Huili (Cancer Manag Res, 2020)
BACKGROUND: Microsatellite instability (MSI) is one of the most important molecular characteristics of colorectal cancer (CRC), which mainly results from defective DNA mismatch repair (MMR). This study was performed to investigate the concordance between deficient MMR and MSI testing, and to evaluate the association of these two results with clinicopathological characteristics in Chinese CRC patients. METHODS: A total of 738 CRC patients were included. Tumor tissues and paired peripheral blood specimens were obtained. Screening for MMR was investigated using immunohistochemical (IHC) technique, and multiple polymerase chain reaction﻿-capillary electrophoresis (PCR-CE) method was performed to detect the MSI status. All clinicopathological data, immunohistochemistry and microsatellite instability analyses were then statistically analyzed. RESULTS: ﻿Of the 738 (17.75%) CRC patients, 131 expressed as deficient mismatch repair (dMMR) status, and postmeiotic segregation increased 2 (PMS2) deficiency was the most frequent deficiency among these four MMR proteins. MSI-high (MSI-H) status occurred in 74 of the 738 (10.03%) CRC patients, 55 of whom showed instability at all six mononucleotides repeat markers. dMMR was significantly associated with MSI-H and moderate concordance was observed between IHC and PCR-CE in evaluating deficient MMR/MSI through Kappa test. Statistically, dMMR was significantly associated with younger age, right-sided colon and poor differentiation. MSI-H was associated with younger age, right-sided colon, poor differentiation, mucinous type and ﻿tumor, ﻿node, ﻿metastasis (TNM) stage II. CONCLUSION: A moderate concordance between deficient MMR and MSI testing indicates that both IHC and PCR-CE methods should be routinely tested to provide reliable data for clinical treatment decisions.